Exploring Teacher Professional Development’s Perceptions of English Secondary School Teachers - Dinata, Uray; Bukhori, Muhammad; Nur’Afif, Sulthon; Atmaja, Bhaskara (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Teacher perceptions in Teacher Professional Development are very important to make teachers more skilled in teaching, managing classes, and relating to school affairs. The experience gained from Teacher Professional Development will have a big impact on any teacher's activities, it's all because of the useful activities that have been designed in Teacher Professional Development. This study aims to find out teachers' perceptions of Teacher Professional Development and how teachers conduct during the COVID-19 pandemic. This research uses descriptive research in the qualitative method. The participants of this research were three junior high school English teachers from various places who had participated in Teacher Professional Developments, the schools were SMP Muhammadiyah 5 Yogyakarta, SMP Negeri 1, 3 and 5 in Selakau, West Kalimantan. Data was collected through an Interview. Findings from this research show that there are three perceptions of a teacher towards Teacher Professional Development (TPD) such as TPD can help teachers to assist students in learning language learning theories, TPD is very helpful for developing teachers' abilities and creativity and TPD can make teachers control the classroom situation by both professionally. Furthermore, there are two ways for teachers to participate in a certain Teacher Professional Development during the COVID-19 pandemic, TPD is done online and TPD assignments are given online. This research concludes that every teacher must participate in Teacher Professional Development because this activity brings many benefits to teachers in teaching and managing school affairs.